LA REPUBLIQUE CENTRAFRICAINE (African Disability Rights Yearbook, 2021)
According to the general Census of Population conducted in December 2003, the Central African Republic population is 3 895 139 million. According to this Census of Population, Persons with disabilities are 50 636, that is 1,3 % of the total population; the most prevalent forms of disabilities include partial paralysis, sensory disabilities such as deaf. The Central African Republic signed the United Nations Convention on the Rights of Persons with Disabilities (CRPD), as well as its Optional Protocol on 11 October 2016. The CRDP was ratified on 11 October 2016 by the Central African Republic government. The Constitution of the Central Africa Republic contains no provision dealing directly with disabilities. The term disability does not openly appear in the Constitution. Nevertheless, the Constitution provides for the right to equality for all, including persons with disabilities. The rights to employment, education, etc, for all, are also guaranteed by the Preamble on the Constitution. The Central African Republic has numerous pieces of legislation that directly address disability. The key ones are Law N°00.007of 20 December 2000 on the promotion and the protection of the rights of persons with disabilities, which has not yet been ratified, the decree N°02.205 of 06 August 2002 that instituted application measures of Law N°00.007of 20 December 2000. The policies that directly address persons with disabilities are: (1) the national policy and its action plan; (2) the national policy of social welfare and its action plan; and (3) the national strategy on the protection of vulnerable children and the national policy on protection of children as well as its action plan including programmes affecting directly people with disabilities.Other than ordinary courts or tribunals, the Central African Republic has no official body that specifically addresses the violation of the rights of people with disabilities. However, on 28 June 2017 the government established a national Human Rights Commission which has to be autonomous, neutral and endowed with a legal entity. It also enjoys administrative, technical and financial autonomy and independence of action. While waiting for the effectivity of the Human Rights Commission, its mandate is discharged by the National High-Commission for Human Rights of Central African Republic. The Central African Republic also has a Human Rights Federation which organises actions on the promotion and protection of persons with disabilities. There are numerous organisations that represent and advocate for the rights and welfare of persons with disabilities in the Central African Republic. They include l’Association Ministère d’Evangélisation; Ensemble pour la Promotion et l’Insertion des Personnes Handicapées; and l’Association Nationale la Main des sourds Muets pour le Travail et le Développement de Centrafrique. In the Central African Republic, the Ministry of National and Higher Education; and the Ministry of Family, Social Work, and National Solidarity are involved in promoting and protecting disability rights. Persons with disabilities in this country face many problems such as the lack of doctors specialised in re-education and rehabilitation. Where access is concerned, persons with disabilities have difficulties in accessing public buildings, public transport, education, vocational training, healthcare, employment justice and other social structures, in practice, very little is done to ensure access for persons with disabilities. The Central African Republic government should strengthen and speed up the implementation of its national policies and programmes for the implementation of disability rights. It should increase the promotion of disability rights especially in the rural areas.